Morcegos do Parque Estadual Carlos Botelho, Sudeste da Mata Atlântica: taxonomia e saúde ambiental - Cláudio, Vinícius Cardoso (Universidade Federal de São Carlos, 2018)
The Atlantic Forest in one of the 25 biodiversity hot spots in the world, but has suffered with a severe exploitation in the past and the biome area was reduced to 8% of its original extent. This fact, associated to the constant threats to the fauna, is pushing many species to the threshold of extinction. Carlos Botelho State Park (CBSP) is a large remnant on the Brazilian southeastern Atlantic Forest, with more than 37000 ha and no previous studies on bats. Therefore we aimed to perform the first bat inventory on CBSP, to provide data on the distribution, natural history and taxonomy of the species, focusing on the external morphology, once many species are externally similar and hard to identify on field. Additionally, we describe the microbiota diversity from oral and rectal cavities of frugivore, nectarivore, insectivore, sanguivore and carnivore bats from CBSP, and their antibiotic-resistance patterns. We conducted monthly fieldworks between October 2016 and September 2017, capturing 412 bats of 34 species of the families Phyllostomidae, Molossidae and Vespertilionidae. Captures were made using ground level mist-nets (39600 m².h), canopy mist-nets (2017.5 m².h) and searches for roosts (42 h). Bacteria were identified using the MALDI-TOF technique and the antibiotic-resistance patterns were evaluated by the Kirby-Bauer’s antibiotic disc diffusion technique on eight selected bacteria. Species rarely sampled on the Atlantic Forest of São Paulo were captured on canopy mist-nets. The species Micronycteris schmidtorum and Molossus currentium were registered for the first time in the state of São Paulo. The elevated number of species captured on CBSP surpasses most of the studies conducted on similar areas, and reinforces the importance of employing mixed capture methodologies, such as elevated mist-nets and searches for roosts. We identified 596 isolates at genus level and tentatively species level. The most common bacteria between groups were Escherichia coli, Klebsiella oxytoca and Serratia marcescens. The frugivore bats presented the most diverse microbiota, followed by the insectivore bats. The general results exhibited a low occurrence of resistant bacteria, which could be related to the effectivity of the Park in conserving the wildlife and environment. Once the major causes of resistance-acquiring are related to antropic activites, the limited access for tourists on certain regions of the Park seems to be effectively protecting the environment.
Keywords: Mata Atlântica; Chiroptera; Microbiota; Distribuição; Morfologia; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES